(untitled) (REMUNOM, 2025)
This article addresses the importance of nursing care in psychiatric units, emphasizing the problems faced by health professionals and pointing out strategies to improve care and health promotion. The study begins by highlighting the complexity of care for patients who have some type of mental disorder, emphasizing the need for a multidisciplinary approach and the importance of empathy and effective communication from nursing professionals. The main obstacles to this problem involve the lack of resources, the stigmas related to mental illnesses today and mainly the need for professional training for nurses who work in the area. The strategies aim to involve continuous training of healthcare teams and the creation of therapeutic environments that can offer safety and comfort to patients, thus providing more effective care and improving the quality of life of psychiatric patients.